THE INFLUENCE OF PSYCHOLOGICAL STATE ON THE FORMATION OF CLINICAL THINKING IN STUDENTS - Yusupova Dildora Uktamovna (American Journals, 2025)
This article examines the influence of the psychological state of medical students on the formation of their clinical thinking. Clinical reasoning is a complex cognitive process that includes important skills such as analyzing the patient's condition, making a diagnosis, and developing a treatment plan. Students' stress, anxiety, fatigue, lack of confidence, and other psychological conditions can negatively affect their clinical reasoning skills. The article analyzes the mechanism of influence of psychological states on clinical thinking, ways to reduce this influence, and the importance of considering psychological factors in clinical education.
Keywords: Clinical thinking, psychological state, stress, anxiety, fatigue, medical students, cognitive process, educational strategy.